Trisubstituted barbiturates and thiobarbiturates: Synthesis and biological evaluation as xanthine oxidase inhibitors, antioxidants, antibacterial and anti-proliferative agents - Figueiredo, Joana (2020)
Barbituric and thiobarbituric acid derivatives have become progressively attractive to medicinal chemists due to their wide range of biological activities. Herein, different series of 1,3,5-trisubstituted barbiturates and thiobarbiturates were prepared in moderate to excellent yields and their activity as xanthine oxidase inhibitors, antioxidants, antibacterial agents and as anti-proliferative compounds was evaluated in vitro. Interesting bioactive barbiturates were found namely, 1,3-dimethyl-5-[1-(2-phenylhydrazinyl)ethylidene]pyrimidine-2,4,6(1H,3H,5H)-trione (6c) and 1,3-dimethyl-5-[1-[2-(4-nitrophenyl)hydrazinyl]ethylidene]pyrimidine-2,4,6(1H,3H,5H)-trione (6e), which showed concomitant xanthine oxidase inhibitory effect (IC50 values of 24.3 and 27.9 μM, respectively), and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity (IC50 values of 18.8 and 23.8 μM, respectively). In addition, 5-[1-(2-phenylhydrazinyl)ethylidene]pyrimidine-2,4,6(1H,3H,5H)-trione (6d) also revealed DPPH radical scavenger effect, with an IC50 value of 20.4 μM. Moreover, relevant cytotoxicity against MCF-7 cells (IC50 = 13.3 μM) was observed with 5-[[(2-chloro-4-nitrophenyl)amino]methylene]-2-thioxodihydropyrimidine-4,6(1H,5H)-dione (7d). Finally, different 5-hydrazinylethylidenepyrimidines revealed antibacterial activity against Acinetobacter baumannii (MIC values between 12.5 and 25.0 μM) which paves the way for developing new treatments for infections caused by this Gram-negative coccobacillus bacterium, known to be an opportunistic pathogen in humans with high relevance in multidrug-resistant nosocomial infections. The most promising bioactive barbiturates were studied in silico with emphasis on compliance with the Lipinski's rule of five as well as several pharmacokinetics and toxicity parameters.